Protein misfolding and clearance in the pathogenesis of a new infantile onset ataxia caused by mutations in PRDX3. Issue 22 (29th June 2022) - Martínez-Rubio, Dolores; Rodríguez-Prieto, Ángela; Sancho, Paula; Navarro-González, Carmen; Gorría-Redondo, Nerea; Miquel-Leal, Javier; Marco-Marín, Clara; Jenkins, Alison; Soriano-Navarro, Mario; Hernández, Alberto; Pérez-Dueñas, Belén; Fazzari, Pietro; et al.
Abstract: Peroxiredoxin 3 (PRDX3) encodes a mitochondrial antioxidant protein, which is essential for the control of reactive oxygen species homeostasis. So far, PRDX3 mutations are involved in mild-to-moderate progressive juvenile onset cerebellar ataxia. We aimed to unravel the molecular bases underlying the disease in an infant suffering from cerebellar ataxia that started at 19 months old and presented severe cerebellar atrophy and peripheral neuropathy early in the course of disease. By whole exome sequencing, we identified a novel homozygous mutation, PRDX3 p.D163E, which impaired the mitochondrial ROS defense system. In mouse primary cortical neurons, the exogenous expression of PRDX3 p.D163E was reduced and triggered alterations in neurite morphology and in mitochondria. Mitochondrial computational parameters showed that p.D163E led to serious mitochondrial alterations. In transfected HeLa cells expressing the mutation, mitochondria accumulation was detected by correlative light electron microscopy. Mitochondrial morphology showed severe changes, including extremely damaged outer and inner membranes with a notable cristae disorganization. Moreover, spherical structures compatible with lipid droplets were identified, which can be associated with a generalized response to stress and can be involved in the removal of unfolded proteins. In the patient's fibroblasts, PRDX3 expression was nearly absent. The biochemical analysis suggested that the mutation p.D163E would result in an unstable structure tending to form aggregates that trigger unfolded protein responses via mitochondria and endoplasmic reticulum. Altogether, our findings broaden the clinical spectrum of the recently described PRDX3 -associated neurodegeneration and provide new insight into the pathological mechanisms underlying this new form of cerebellar ataxia.